Seasonal profile of the diet of the dace Telestes karsticus Marčić & Mrakovčić, 2011 (Cyprinidae, Leuciscinae) endemic to Sušik Creek, Croatia. (30th May 2017) - Marčić, Z.; Sučić, I.; Ćaleta, M.; Buj, I.; Mustafić, P.; Zanella, D.
Summary: The first data on the feeding ecology of the endemic Telestes karsticus are presented for specimens sampled monthly (July 2007–July 2008) from the Sušik Creek in the Lug Polje field, Croatia. Macrozoobenthos density was calculated and compared with the stomach contents of T. karsticus and the seasonal profile of the diet was examined. The ratio of gut length vs. standard length was 0.9 ± 0.12. Gut contents revealed that benthic invertebrates accounted for the majority of food consumed, although terrestrial arthropods, plant material, algae and fish were also found. Since this is the only fish species in the investigated creek, T. karsticus can be concluded to be cannibalistic. The proportion of empty guts found in all seasons was small, indicating year round feeding. The number and diversity of prey species was highest in spring and lowest in summer. Ivlev's electivity index was very high for Cladocera, Coleoptera, Trichoptera, Heteroptera and Hymenoptera in all seasons, suggesting positive selection for these prey groups, as opposed to Oligochaeta, Isopoda and Bivalva, which showed negative values in all seasons. For Actinopterygii, the Ivlev coefficient of selection was highly negative in spring, and highly positive in summer. Plant matter was detected in stomach contents in all seasons, with the highest share found in summer when other prey species were less available. The karstic dace is a generalised feeder, consuming the most available prey, and therefore can be classified as a euryphagous omnivore.